Research Progress of PROTAC-Degraded CDKs in the Treatment of Breast Cancer - Zhao K; Zhang J; Yang Z; Wang R; Shi Y; Ji Y; Zhang S; Liu M (Breast Cancer: Targets and Therapy, 2025)
Kexin Zhao,1 Jun Zhang,1 Zhe Yang,1 Rong Wang,1 Yuhuan Shi,1 Yanan Ji,1 Shengjun Zhang,2 Minli Liu1 1Yan’an Medical College of Yan’an University, Yan’an, People’s Republic of China; 2Department of General Surgery, Yan’an University Affiliated Hospital, Yan’an, People’s Republic of ChinaCorrespondence: Shengjun Zhang, Email zsj@yau.edu.cn Minli Liu, Email lml@yau.edu.cnAbstract: Breast cancer (BC) is the most common type of cancer among women worldwide. A large number of studies have found that the high expression or dysregulation of cyclin-dependent protein kinases (CDKs) is closely associated with breast cancer. For example, the CDK4/6-Rb axis is involved in the G1/S phase transition of the cell cycle and plays an important role in BC; CDK1 and its associated cyclin are commonly involved in mitotic progression, and increased expression of CDK1-associated cyclin has been observed in BC; loss of CDK12 significantly ameliorates triple-negative breast cancer. CDKs are one of the major families within the group of PROteolysis Targeting Chimeras (PROTACs)-degraded kinases. PROTAC is a potent technology for protein-targeted degradation, whose molecules consist of the ligand of the Protein of Interest (POI), the ligand of the E3 ubiquitin ligase (E3), and a Linker. After binding to POI, PROTAC can recruit E3 to ubiquitinate POI via ubiquitin-proteasome mediated degradation. In this review, we summarize relevant research results and review that PROTAC can effectively inhibit the proliferation of breast cancer cells by inducing ubiquitination of CDK1, CDK4/6, CDK9, CDK12/13 and their subsequent degradation by proteasomes, which is expected to be a novel approach for the treatment of breast cancer.Keywords: breast cancer, ubiquitin, PROTAC, CDKs